Observation, theory and modeling of atmospheric variability : selected papers of Nanjing Institute of Meteorology Alumni in commemoration of Professor Jijia Zhang / [Edited by] Xun Zhu
This book contains tutorial and review articles as well as specific research letters that cover a wide range of topics: (1) dynamics of atmospheric variability from both basic theory and data analysis, (2) physical and mathematical problems in climate modeling and numerical weather prediction, (3) theories of atmospheric radiative transfer and their applications in satellite remote sensing, and (4) mathematical and statistical methods. The book can be used by undergraduates or graduate students majoring in atmospheric sciences, as an introduction to various research areas; and by researchers a.